Financial and economic performance of the dairy industry of Ukraine - Arych, Mykhailo; Gnatenko, Elena (My University, 2014)
Analysis of financial and economic performance of dairy enterprises is important to determine the overall status and quality of their operations and predict trends.
Keywords: income; dynamics; dairy; enterprise; дохід; динаміка; молоко; підприємство; доход; динамика; предприятие; кафедра фінансів